THE MAGMATIC EVOLUTION OF THE LAND'S END PLUTON, CORNWALL, AND ASSOCIATED PRE-ENRICHMENT OF METALS - Müller A.; Seltmann R.; Halls C.; Jeffries T.; Spratt J.; Siebel W.; Dulski P.; Kronz A. (My University, 2006)
The peraluminous Land's End granite is one of the composite plutons forming the late-Variscan Cornubian batholith. The western part of the pluton hosts the Sn-Cu mineralisation of the St. Just mining district. The pluton consists of early megacrystic biotite (Mg-siderophyllite) granites and albite microgranites and younger Li-siderophyllite granites, and tourmaline granites together with fine-grained massive quartz-tourmaline rocks (MQT). Most of the granite varieties evolved by fractional crystallisation from a common crustal magmatic reservoir, apart from the albite microgranite, which has a different source. Trace element analyses of K-feldspar megacrysts in the older biotite granites made using laser ablation ICP-MS reveal that the megacrysts were derived from moderately evolved sources and now reside in separate granite sub-stages with variable degrees of fractionation, so that equilibrium between phenocrysts and host no longer persists. The younger granites show a strong in situ fractionation at the cm- to 100-m-scale, whereby boron-rich melts are concentrated in the apical parts of the individual intrusive units. Geological, textural and mineralogical data suggest that the tourmaline granites and MQT evolved mainly from fractionated Li-siderophyllite granites. Cathodoluminescence, trace element and melt inclusion studies of quartz from the MQT reveal that the MQT was formed during the transition from the magmatic to hydrothermal states from a mixture of immiscible phases. The Li-siderophyllite granites, tourmaline granites and MQT appear to be the immediate magmatic precursors from which the hydrothermal fluids responsible for the mineralisation in the St Just district originated. © 2005 Elsevier B.V. All rights reserved.
Keywords: CORNWALL; LA-ICP-MS; LAND'S END GRANITE; PERALUMINOUS; POTASSIUM FELDSPAR; REE; TOURMALINE